Bacterial Anti-Adhesion of Coated and Uncoated Thin-Film-Composite (TFC) Polyamide (PA) Membranes - Nikkola, Juha; Alakomi, Hanna-Leena; Tang, Chuyang Y. (Journal of Coating Science and Technology, 2014)
This study investigates the bacterial anti-adhesion performance of uncoated and coated reverse osmosis (RO) membranes. All the membranes were commercially available fully-aromatic thin-film-composite (TFC) polyamide (PA) membranes. Two of the TFC PA membranes (SW30 and BW30) were coated using polyvinyl alcohol (PVA) coating, while the other three membranes (LE, XLE and NF90) were uncoated. Among the characterised TFC PA membranes, the PVA coated were more hydrophilic and their surface energy was higher in comparison to uncoated. In addition, the PVA coated membranes had lower surface roughness. AFM interaction force measurement demonstrated higher repellence performance for the more polar surface. Bacteria attachment test showed differences between the coated and the uncoated membranes. Indeed, the increase in hydrophilicity and surface polarity showed decrease in the attachment of Pseudomonas aeruginosa cells. Moreover, the results demonstrated that the surface polarity showed better correlation with the attachment of the bacteria. In addition, the type of the surface roughness may somehow contribute to the bacteria repellence.